The First Treachery of the West. On the Book by Andrzej Nowak - Kornat, Marek (Kwartalnik Historyczny, 2018)
The Polish-Soviet War (1919–20) is one of the key events in the process of implementation of the Versailles order in Eastern Europe. Having saved the Versailles deal, the war gave the nations of Central and Eastern Europe an extremely valuable opportunity, for twenty years, to decide about themselves and build their own nation states on the remnants of three empires, which disintegrated in the aftermath of the geopolitical revolution brought by the Great War (1914–18). From the very beginning, the West did not understand the geopolitical significance of the Polish-Soviet War, seen as a local conflict of two countries, triggered by ‘Polish imperialism’.